2011
DOI: 10.1002/sca.20251
|View full text |Cite
|
Sign up to set email alerts
|

Forensic surface metrology: tool mark evidence

Abstract: Over the last several decades, forensic examiners of impression evidence have come under scrutiny in the courtroom due to analysis methods that rely heavily on subjective morphological comparisons. Currently, there is no universally accepted system that generates numerical data to independently corroborate visual comparisons. Our research attempts to develop such a system for tool mark evidence, proposing a methodology that objectively evaluates the association of striated tool marks with the tools that genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 24 publications
(29 reference statements)
0
27
0
Order By: Relevance
“…Many other metrics for quantifying pattern similarity for firearms evidence exists [4–7]. At the National Institute of Standards and Technology (NIST) a method called Congruent Matching Cells (CMC) has been developed [3].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many other metrics for quantifying pattern similarity for firearms evidence exists [4–7]. At the National Institute of Standards and Technology (NIST) a method called Congruent Matching Cells (CMC) has been developed [3].…”
Section: Methodsmentioning
confidence: 99%
“…The approaches to addressing the issues raised by the report [2] generally fall into two categories. The first is to develop measurement systems and computer algorithms that are able to quantify the degree of similarity between tool marks [3–7]. Using these systems and an appropriately selected, representative database of firearms evidence, it is possible to estimate error rates for comparisons and obtain consistent, objective similarity scores.…”
Section: Introductionmentioning
confidence: 99%
“…These research efforts have shown that topography measurements in 3D allow good accuracy, while at the same time, maintaining a high level of reproducibility. The main objectives of the statistical analysis carried out in these previous studies were either to measure the global discrimination power of the 3D system, establishing the respective error rates (often used to assess the discrimination power of the analyzed impressions) , or to measure the efficiency of these systems when they are used in the context of a database search . The objective of the present study is different as it aims to obtain an objective assignment of the weight of the evidence derived from a set of observations between two entities measured in 3D.…”
Section: Purpose Of the Researchmentioning
confidence: 99%
“…As a "frequentist"-based approach to association quality, conformal prediction theory is used to assign orthodox confidence levels to each toolmark identification. This is accomplished via Vovk, Gammerman, and Shafer's (2005) formula for a nonconformity measure using the SVM Lagrange multipliers (Gambino et al, 2011;Petraco et al, 2012). As a test of the method's validity, on-line prediction plots are constructed for successive toolmark identifications.…”
Section: Abstract: Chemometrics Comparison Graffitimentioning
confidence: 99%